Local Politics, Budgets and Development Programmes in Croatia - Marijana Sumpor (European Regional Science Association (ERSA), 2004)
If the political climate is stable, local elections in Croatia take place every four years. Budgets are planned for three years, while strategic development programmes cover periods of five to ten years. Technically, the political, financial and developmental programming cycles can be matched, and implementation of the programmes ensured. However, political programmes are generally vague, budgets are every so often fictive and revised mid year and development programmes grow into visionary shopping lists. Reality shows that programmes and plans are elaborated, presented in public and then neatly put into drawers. In the aftermath, local politicians are concerned mainly about the financing flows and this is what they are usually fighting for at council meetings and in various ministries. Regularly, local administration proceeds according to the wishes of the political decision makers, without referring to any program in the end. Consequently, political accountability is lacking, fiscal management is not transparent and development is lagging behind. The main aim of this paper is to show how strategic development programmes, budgetary plans and political programmes can be linked in the Croatian socio-economic and institutional environment. Also, in line with the initiated process of decentralization in Croatia, local governments have to improve their fiscal management in order to be able to take over new functions and responsibilities. Since by now a number of local development programmes exist in Croatia, where a participatory and strategic development planning approach was applied, an analysis of the political programmes, local budgets and development programmes can be done. The purpose of this research is to demonstrate that if local governments better understood the interdependencies between these three segments, they could create reference points for their actions visible in their programmes and budgets. In this way a platform could be created to enhance the political accountability, improve fiscal capacity and fulfil developmental goals in line with real needs and potentials of the local population.
Keywords: 330